2019
DOI: 10.1371/journal.pone.0214732
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination status and associated factors among undergraduate students of Makerere University College of Health Sciences

Abstract: Background Hepatitis B is a global health problem. Trainees in the health-related fields are exposed to occupational risk of Hepatitis B Virus. In Uganda, there is scarcity of information on vaccination among students in health-care. The objective of this study was to assess hepatitis B vaccination status of the students and factors associated. Methods and findings This was a cross sectional study, conducted at Makerere University College of Health Sciences among underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
27
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 5 publications
12
27
6
Order By: Relevance
“…The rate for full vaccination among our respondents was lower than the rate reported among HCSs in Greece [30] but higher than that found in a study among medical students in Cameroon which showed a complete vaccination rate of 16.8% [31]. Non-vaccination in our study was reported by 14.3% of respondents which was lower than the 33.2% found among students in Uganda [36]. The existence of a vaccination program which encourages the uptake of the vaccine at KMTC could explain the lower non-vaccination rates.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The rate for full vaccination among our respondents was lower than the rate reported among HCSs in Greece [30] but higher than that found in a study among medical students in Cameroon which showed a complete vaccination rate of 16.8% [31]. Non-vaccination in our study was reported by 14.3% of respondents which was lower than the 33.2% found among students in Uganda [36]. The existence of a vaccination program which encourages the uptake of the vaccine at KMTC could explain the lower non-vaccination rates.…”
Section: Discussioncontrasting
confidence: 85%
“…The respondents' year of study and duration at KMTC were significantly associated with vaccine uptake. These findings are similar to those found among university students in Malaysia and Uganda [36,37]. This is probably associated with the increased awareness of HBV by senior students as more coursework has been covered, as well as being in the college for a longer time, which would offer more opportunities for vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…The rate for full vaccination among our respondents was lower than the rate reported among HCSs in Greece (31) but higher than that found in a study among medical students in Cameroon which showed a complete vaccination rate of 16.8% (32). Non-vaccination in our study was reported by 14.3% of respondents which was lower than the 33.2% found among students in Uganda (37). The existence of a vaccination program which encourages the uptake of the vaccine at KMTC could explain the lower non-vaccination rates.…”
Section: Discussioncontrasting
confidence: 85%
“…The respondents' year of study and duration at KMTC were significantly associated with vaccine uptake. These findings are similar to those found among university students in Malaysia and Uganda (37,39). This is probably associated with the increased awareness of HBV by senior students as more coursework has been covered, as well as being in the college for a longer time, which would offer more opportunities for vaccination.…”
Section: Discussionsupporting
confidence: 83%
“…This study showed that young psychoactive substance users with a higher level of income were more likely to screen for hepatitis B compared to those who had a lower level of income. This could be attributed to the high cost of accessing hepatitis B prevention services (43). In some situations, health facilities providing these services are located further away from informal settlements.…”
Section: Discussionmentioning
confidence: 99%